The pattern of contact lens usage among university community: A crosssectional study in UiTM Puncak Alam/ Nadia Emylia Zairolanuar and Fatin Nur Najwa Norazman - Zairolanuar, Nadia Emylia; Norazman, Fatin Nur Najwa (Faculty of Health Sciences, Universiti Teknologi MARA, 2019)
The cross-sectional study was conducted to find a pattern of contact lens usage among university community and problems related to its use. Two hundred and fifty-two participants among the university community in UiTM Puncak Alam that fulfil inclusion criteria were given a set of questionnaire consists of 22 items to be answered. Results showed that 81.3% of respondents are current contact lens users, with females (81%) outnumbered males in lens wear. Most preferred contact lens type was soft-disposable (73.8%), while most quoted reasons for usage were convenience (61.5%) and comfort (17.9%). Symptoms like dry eyes, red eyes, and watery eyes were the most reported problems faced by the wearers. There was no association between pattern of contact lens usage with contact lens complications. Even though majority of wearers do not have issues with contact lens, problems associated with its wear continue to persist in this study as 33.4% of them experienced problems related to its wear. Even though most participants did not have issues associated with CL use, awareness of lens care and hygiene needed to be increased to avoid any eye complications in the future.